Can Bodybuilding Peak Week Manipulations Favorably Affect Muscle Size, Subcutaneous Thickness, and Related Body Composition Variables? A Case Study - Christopher Barakat; Guillermo Escalante; Scott W. Stevenson; Joshua T. Bradshaw; Andrew Barsuhn; Grant M. Tinsley; Joseph Walters (MDPI AG, 2022)
Background: The purpose of this case study was to implement an evidence-based dietary approach to peaking for a bodybuilding competition and monitor its impact on body composition, muscle thickness (MT), intra-to-extra-cellular fluid shifts, subcutaneous thickness (ST), and hydration status. Secondarily, to document any adverse events of this peak week approach in a small, controlled setting. Methods Dietary practices were recorded, and laboratory testing was conducted throughout peak week, including competition morning. Assessments included: dual-energy X-ray absorptiometry (DEXA) for body composition, B-mode ultrasound for MT and ST, bioimpedance spectroscopy (BIS) for total body water (TBW)/intracellular water (ICW)/extracellular water (ECW), and raw BIS data (i.e., resistance, reactance, and phase angle), urine specific gravity (USG) for hydration status, and subjective fullness. Sequential dietary manipulations were made (i.e., CHO depletion/fat loading, CHO/water loading, and a refinement phase) with specific physiological goals. This was reflected in changes observed across all assessments throughout the peak week. Results: From the carbohydrate-depleted state (three days out) to competition day, we observed increases in lean body mass, MT, TBW (primarily ICW), and subjective fullness. Kendall's Tau B revealed a strong relationship between carbohydrate intake and ∑MT (τ = 0.733, p = 0.056). Additionally, novel ST data demonstrated a 10% reduction for the summation of all seven sites, with some drastic changes in specific regions (e.g., −43% for triceps ST) from three days out to competition day. Conclusions: These data suggest that the prototypical goals of bodybuilders' peak week (i.e., increasing muscle fullness, decreasing subcutaneous thickness) to enhance their aesthetics/muscularity presented can be achieved with a drug-free protocol involving dietary manipulations.